Stibiogoldfieldite, Cu12(Sb2Te2)S13, a new tetrahedrite-group mineral. (7th February 2022) - Biagioni, Cristian; Sejkora, Jiří; Musetti, Silvia; Makovicky, Emil; Pagano, Renato; Pasero, Marco; Dolníček, Zdeněk
ABSTRACT: Stibiogoldfieldite, Cu12 (Sb2 Te2 )S13, was approved as a new mineral species from the Mohawk mine, Goldfield mining district, Esmeralda County, Nevada, USA. It occurs as metallic anhedral grains, dark grey in colour. It is associated with quartz, pyrite and an Ag–Bi–(S, Se) phase (holotype material) and with quartz, pyrite, calaverite, bismuthinite, bohdanowiczite, and the Ag–Bi–(S, Se) phase (cotype material). In reflected light, stibiogoldfieldite is isotropic, grey in colour, with indistinct brownish shade. Reflectance data in air [ R (%)] are: 31.1 at 470 nm, 30.9 at 546 nm, 30.8 at 589 nm and 31.0 at 650 nm. Electron microprobe analysis for holotype material gave (in wt.% – average of 60 spot analyses): Cu 45.03(60), Ag 0.26(7), Fe 0.02(3), Zn 0.13(15), Sn 0.02(4), Pb 0.05(6), Sb 8.02(62), As 2.80(65), Bi 2.77(87), Te 15.15(1.24), S 24.50(32), Se 0.52(11), total 99.27(69). On the basis of (As + Sb + Te + Bi) = 4 atoms per formula unit (apfu), the empirical formula of stibiogoldfieldite is (Cu12.05 Ag0.04 Zn0.03 Fe0.01 )Σ12.13 (Sb1.12 As0.63 Bi0.23 Te2.02 )Σ4.00 (S12.99 Se0.11 )Σ13.10 . Chemical data on an additional sample from the same locality (cotype material) gave the following results (in wt.% – average of 181 spot analyses): Cu 43.84(63), Ag 0.21(7), Sb 5.92(78), As 2.63(45), Te 20.07(1.19), S 25.13(53), Se 0.97(35), total 99.47(66). On the basis of (As + Sb + Te + Bi) = 4 apfu, the empirical formula of cotype material is (Cu11.30 Ag0.03 )Σ11.33 (Sb0.80 As0.57 Bi0.06 Te2.57 )Σ4.00 (S12.83 Se0.20 )Σ13.03 . Stibiogoldfieldite is cubic, I $\overline 4$ 3 m, with unit-cell parameters a = 10.3466(17) Å, V = 1107.6(5) Å 3 and Z = 2 (holotype). Unit-cell parameters for the cotype sample are a = 10.3035(2) Å and V = 1093.83(7) Å 3 . The crystal structure of holotype stibiogoldfieldite was refined by single-crystal X-ray diffraction data to a final R 1 = 0.032 on the basis of 285 reflections with F o > 4σ( F o ) and 20 refined parameters. Stibiogoldfieldite is isotypic with other members of the tetrahedrite group.